Real‐time PCR detection of Didemnum perlucidum (Monniot, 1983) and Didemnum vexillum (Kott, 2002) in an applied routine marine biosecurity context. (29th August 2016) - Simpson, Tiffany J. S.; Dias, P. Joana; Snow, Michael; Muñoz, Julieta; Berry, Tina
Abstract: Prevention and early detection are well recognized as the best strategies for minimizing the risks posed by nonindigenous species (NIS) that have the potential to become marine pests. Central to this is the ability to rapidly and accurately identify the presence of NIS, often from complex environmental samples like biofouling and ballast water. Molecular tools have been increasingly applied to assist with the identification of NIS and can prove particularly useful for taxonomically difficult groups like ascidians. In this study, we have developed real‐time PCR assays suited to the specific identification of the ascidians Didemnum perlucidum and Didemnum vexillum . Despite being recognized as important global pests, this is the first time specific molecular detection methods have been developed that can support the early identification and detection of these species from a broad range of environmental sample types. These fast, robust and high‐throughput assays represent powerful tools for routine marine biosecurity surveillance, as detection and confirmation of the early presence of species could assist in the timely establishment of emergency responses and control strategies. This study applied the developed assays to confirm the ability to detect Didemnid eDNA in water samples. While previous work has focused on detection of marine larvae from water samples, the development of real‐time PCR assays specifically aimed at detecting eDNA of sessile invertebrate species in the marine environment represents a world first and a significant step forwards in applied marine biosecurity surveillance. Demonstrated success in the detection of D. perlucidum eDNA from water samples at sites where it could not be visually identified suggests value in incorporating such assays into biosecurity survey designs targeting Didemnid species.